2023
DOI: 10.1200/jco.23.00045
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes After Preoperative Chemoradiation With or Without Pazopanib in Non-Rhabdomyosarcoma Soft Tissue Sarcoma: A Report From Children's Oncology Group and NRG Oncology

Aaron R. Weiss,
Yen-Lin Chen,
Thomas J. Scharschmidt
et al.

Abstract: Clinical trials frequently include multiple end points that mature at different times. The initial report, typically based on the primary end point, may be published when key planned co-primary or secondary analyses are not yet available. Clinical Trial Updates provide an opportunity to disseminate additional results from studies, published in JCO or elsewhere, for which the primary end point has already been reported. ARST1321 was a phase II study designed to compare the near complete pathologic response rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Published 3 years later, 3-year event-free survival and overall survival was not significantly different. But there was a trend towards better OS in the group with higher necrosis [ 27 ]. The authors concluded that pathologic necrosis may not accurately measure treatment response but may reflect the tumor biology itself.…”
Section: Discussionmentioning
confidence: 99%
“…Published 3 years later, 3-year event-free survival and overall survival was not significantly different. But there was a trend towards better OS in the group with higher necrosis [ 27 ]. The authors concluded that pathologic necrosis may not accurately measure treatment response but may reflect the tumor biology itself.…”
Section: Discussionmentioning
confidence: 99%
“…Historically, North American pediatric NRSTS studies have used the POG grading system, 7,8,24 although there is widespread acknowledgment among pediatric pathologists that updates are needed given diagnostic advances since its publication nearly 30 years ago. The FNCLCC grading system also has predictive value in pediatric NRSTS, 25 has been used in pediatric NRSTS trials in Europe 2 and North America, 4 and is the de facto grading system for pediatric NRSTS worldwide. However, our analysis suggests that using FNCLCC grading would result in nearly a third of our low‐risk, surgery‐only patients receiving adjuvant radiotherapy and/or chemotherapy using either the ARST0332 5 or the EpSSG NRSTS2005 2 treatment approach.…”
Section: Discussionmentioning
confidence: 99%
“…Non-rhabdomyosarcoma soft tissue sarcomas (NRSTS) account for approximately 60% of pediatric soft tissue sarcomas (STS). 1 Histologic grade is a predictor of outcome in pediatric and adult NRSTS, [2][3][4] but prospective data on the clinical features and outcomes of patients with low-grade tumors are limited. Children's Oncology Group (COG) study ARST0332 5 validated a novel risk stratification and therapeutic approach for young NRSTS patients based on metastatic status, tumor diameter, histologic grade, extent of surgical resection, and microscopic margin status.…”
Section: Introductionmentioning
confidence: 99%
“…Pazopanib is approved by the US Food and Drug Administration (USFDA) for patients with metastatic renal cell carcinoma and those with metastatic or locally advanced unresectable soft-tissue sarcoma (STS) who experienced progression after chemotherapy ( 7 ). Several trials in patients with localized high-risk extremity STS have also explored the utility of administering neoadjuvant pazopanib with preoperative radiation therapy (RT) with mixed results ( 8 , 9 ). The patient presented in the current study was consuming elderberry supplements when she started pazopanib.…”
Section: Introductionmentioning
confidence: 99%